Tooth bleaching in the maxilla - Delvis Paez Delgado; Ledis Sabina Díaz Sánchez; Maria Isabel Jiménez Castellanos (Centro Provincial de Información de Ciencias Médicas, 2019)
The case report of a 28 year-old patient  who went to the comprehensive care service of  Mártires del Moncada Provincial Teaching Stomatological Clinic in Santiago de Cuba for presenting a change of color in the anterosuperior left tooth is described.  Periapical X-ray was indicated that showed  pulpar radicular treatment  in that tooth. It was decided to carry out the blenching technique for dyschromia of organic origin for 3 or 4 sessions.  The expected result was obtained and the patient was satisfied.